Peripheral Thought: Intellectualities Beyond the Center - Deves-Valdes, E (Springer, 2021)
This chapter presents a conversation between Eduardo Devés and Andrés Kozel. Of Chilean origin, Devés is one of the few authors who treats peripheral thought (or the Global South) as a whole. In this exchange, Devés addresses the main issues explored in his books Pensamiento periférico and Estudios eidéticos (not yet translated into English): the common denominators or patterns of peripheral thought; the tension/alternance between centralitarian and identity-based attitudes; the possibilities and limits of the circulation of ideas among the intelligences of the Global South. Some of the main theoretical and methodological challenges of this type of studies are explored, and considerations are made around the notion of “eidetic development” and the links between ideas and development in our time. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2021.